In situ high temperature atomic level studies of large closed grain boundary loops in graphene - Gong, C; He, K; Chen, Q; Robertson, A; Warner, J (American Chemical Society, 2016)
We use an in situ heating holder within an aberration corrected transmission electron microscope (AC-TEM) to study the structure and dynamics of large closed grain boundary (GB) loops in graphene at the atomic level. Temperatures up to 800 °C are used to accelerate dynamic evolution of the defect clusters, increasing bond rotation and atomic addition/loss. Our results show that the large closed GB loops relax under electron beam irradiation into several isolated dislocations far apart from each other. Line defects composed of several adjacent excess-atom clusters can be found during the reconfiguration process. Dislocation ejection from the closed GB loops are seen in real time and are shown to help the reduction in loop size. These results show detailed information about the stability and behavior of large GB loops in 2D materials that have importance in the high temperature processing of these materials.